Digital Divide di Daerah Kepulauan: Hambatan dan Peluang dalam Transformasi Digital Pelayanan Publik di Kabupaten Halmahera Utara - Rumasukun, Armilla; Uang, Yulinda; Kaloly, John Haart; Tondo, Simson (FIA Unkris Press, 2026)
The Indonesian government is currently promoting the use of information and communication technology (ICT) in the provision of public services through the Electronic-Based Government System (EBGS). However, the implementation of digitalization is not yet evenly distributed, espeially in island regions. This is because the digital divide still exists between urban and island regions. This study aims to determine the form of the digital divide in island regions, the obstacles faced, and opportunities that can be utilized to accelerate the digital transformation of public services in North Halmahera Regency. This study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentatio. The research results refer to fourdimensions, namely Material Access, Skills Access, Motivation Access, and Utilization Access. Material access shows that several island in North Halmahera Regency still have difficulty accessing the internet due to limited digital infrastructure. Skills access shows that some island communities do not yet have an understanding of how to use digital devices. Motivation access shows that some island communities have low interest in using technology. Utilizaton access shows that some island communities have not utulized to accelerate the digital-based services. This study also found opportunities that can be utilized to accelerate the digital transformation of public services in North Halmahera Regency, namely by expanding internet network access, building network towers, and digital outreach and training for the community. Therefore, collaboration between the government and the community is needed to reduce the digital divide and improve the quality of public services in island areas